Production and characterization of zeolite from fly ash by xrd (2014)
By classical alkaline hydrothermal process, Zeolites were synthesized from fly ashes coming from a thermo electrical power plant. This process consisted on the reaction between the ash’s inorganic oxides (primarily aluminum and silicon oxides, which according to the characterization of the fly ash exceeded 80% of the sample) and NaOH in different concentrations in a batch reactor. Zeolites obtained were characterized by x-ray diffraction (XRD) analysis, which determines the crystalline phases that have been obtained. The results show the formation of zeolite Na-P and Na-A, this last being of higher interest because of its wide industrial applications. Since the Si/Al ratio is a determining factor in the type of zeolite to obtain, during the synthesis process reaction parameters like temperature, digestion time, NaOH concentration and solid-liquid ratio have been varied, with the goal of increase the concentration of zeolite Na-A in the product.